The Paranthrenini of Mainland China (Lepidoptera, Sesiidae) - Kallies, Axel; Arita, Yutaka; Owada, Mamoru; Wu, Guo-Yi; Wang, Min (Zootaxa, 2014)
We here briefly review the Paranthrenini fauna of Mainland China and provide a checklist of 21 species for this region. We describe six new species: Paranthrene rubomacula Kallies & Owada sp. nov., Nokona opaca Kallies & Wang sp. nov., Nokona bractea Kallies & Arita sp. nov., Scoliokona nanlingensis Kallies & Arita sp. nov., Scoliokona spissa Kallies & Arita sp. nov., Scoliokona shimentai Kallies & Wu sp. nov. Furthermore, we provide numerous new combinations of species formerly associated with the genus Paranthrene in South East Asia, with 12 species transferred to Nokona Matsumura, 1931, 4 to Scoliokona Kallies & Arita, 1998, and one to Cyanosesia Gorbunov & Arita, 1995 (comb. nov.). The genus name Aritasesia Nakamura, 2009 (syn. nov.) is considered a junior subjective synonym of Nokona Matsumura, 1931.